Expression of integrins in cerebral arteriovenous and cavernous malformations - (:unkn) unknown (My University, 2006)
OBJECTIVE: To assess and compare levels and patterns of expression for integrins alphavbeta1, alphavbeta3, and alphavbeta5 in arteriovenous malformations (AVMs) and cavernous malformations (CCMs) of the brain. MATERIALS AND METHODS: Specimens from 10 AVM and 10 CCM lesions were selected from 112 patients with AVMs and 97 patients with CCMs who were treated microsurgically in the Department of Neurosurgery, Marmara University, Istanbul, Turkey. Sections were immunohistochemically stained with antibodies for integrins alphavbeta1, alphavbeta3, and alphavbeta5. Separate histological layers of the vascular wall were evaluated, and levels of expression were graded using a four-tier system. RESULTS: Integrin alphavbeta1 was more strongly expressed in AVMs than in CCMs. This difference was most pronounced in the endothelium and subendothelium/media. Integrin alphavbeta3 was more strongly expressed in CCM endothelium than in AVM endothelium (average grades, 0.9 and 0.4, respectively). All 10 of the CCM lesions expressed integrin alphavbeta5 in the endothelium, whereas only five of the AVMs showed minimal expression of this molecule in the endothelium. CONCLUSION: Current scientific understanding of the roles integrins play in angiogenesis is far from complete. The levels and patterns of expression for these molecules in the histological layers of the vascular walls of AVMs and CCMs provide some clues about the complex biological activities of integrins in these lesions. If one accepts the premise that immunohistochemistry has its inherent methodological problems, integrins alphavbeta1, alphavbeta3, and alphavbeta5 are expressed in AVMs and CCMs in different ways that may be linked to stages of angiogenic maturation. Integrin alphavbeta1 is expressed more strongly in endothelium and subendothelium/media of AVMs than in the corresponding layers of CCMs. Integrins alphavbeta3 and alphavbeta5 are expressed more strongly in CCM endothelium than in AVM endothelium. In addition, integrin alphavbeta5 staining was stronger in CCM subendothelium than AVM subendothelium/media.
Keywords: Adult; Humans; Middle Aged; Immunohistochemistry; Staining and Labeling; Endothelium, Vascular; Intracranial Arteriovenous Malformations; Tissue Distribution; Hemangioma, Cavernous, Central Nervous System; Integrin alphaVbeta3; Integrins; Receptors, Vitronectin; Tunica Media